Involuntary detention and compulsory treatment of non-adherent tuberculosis patients in Kenya: an ethical discourse - Muigano, Martin Ng’ang’a (International Journal Of Community Medicine And Public Health, 2016)
Tuberculosis (TB) is a major public health problem in sub-Saharan Africa due to its highly infectious nature and co-infection with HIV/AIDS. The Kenyan government has implemented various programs and strategies to control TB including the controversial jailing of patients lost to follow-up. In 2010, a Kenya court detained, in a prison facility, two TB patients who were non-adherent to treatment. A similar incidence occurred in 2016 when another TB patient who refused to adhere to TB treatment was jailed. This article analyses the ethical implications of these interventions. It is argued that jailing of patients non-adherent to TB treatment may be in contravention to the ethical principles of autonomy, justice, and equity. A central argument of this article is that incarceration not only contravenes the internationally recognized human rights to autonomy and self-determination but also predisposes the poor population to further risks of TB infection and re-infection thus depriving them of social justice and equity. The principle of the overall benefit to the society is also explored in the context of the Kenyan cases. It is further argued that mandatory isolation strategies may not only be ineffective but also inappropriate and as such, alternative isolation strategies are suggested. The need to streamline the Kenyan health system to accommodate cases of isolation is recommended.